Effect on Soil Properties and Crop Yields to Long-Term Application of Superabsorbent Polymer and Manure - Yang, Yonghui; Wu, Jicheng; Du, Yan-Lei; Gao, Cuimin; Tang, Darrell W. S.; van der Ploeg, Martine (Frontiers in Environmental Science, 2022)
Intensive farming leads to soil degradation, and poses a serious threat to agricultural yield sustainability and soil ecology. Superabsorbent polymer (SAP) and organic manure (OM) are amendments that can remediate soil, and improve the soil structure and soil pore characteristics, thereby enhancing soil quality and promoting crop growth. These benefits may be enhanced through long-term continuous application of the amendments. X-ray computed tomography (CT) was used to determine the number, connectivity, and locations of pores (160-1000 µm, >1000 µm) in the soil at depths of 0-100 cm. Soil organic carbon content, proportion of water-stable macroaggregates (>0.25 mm) (WSM), soil bulk density, field water capacity, available water content, wilting point content, and saturated hydraulic conductivity were also determined. Compared to the control, long-term SAP and OM treatments significantly increased the soil pore number, porosity (10-20 cm), total organic carbon (10-20 cm and 40-50 cm), field water capacity (0-20 cm), available water content (0-20cm), wilting point (10-30 cm), saturated water content (10-70 cm), saturated hydraulic conductivity (0-90 cm), and WSM (0-30 cm and 40-50 cm) while decreasing the soil bulk density (0-70 cm). Compared to OM, SAP had greater beneficial effects on the total organic carbon, soil field water capacity, available water content, saturated water content, saturated hydraulic conductivity, and WSM in soil at 0-20 cm depth. Therefore, the improvements to soil quality benefited an increase in the yields of wheat and maize. SAP and OM were effective at improving soil properties and increasing economic yeild of wheat and maize, the action of SAP is greater than that of OM.